Facilitators and barriers influencing weight management behaviours during pregnancy: a meta-synthesis of qualitative research - Tamara Escañuela Sánchez; Sarah Meaney; Caroline O'Connor; Laura Linehan; Keelin O'Donoghue; Molly Byrne; Karen Matvienko-Sikar (BMC, 2022)
Abstract Background Obesity and overweight are considered risk factors for a range of adverse outcomes, including stillbirth. This study aims to identify factors reported by women influencing weight management behaviours during pregnancy. Methods A systematic search was conducted in five databases from inception to 2019 and updated in 2021. Qualitative studies involving pregnant or post-partum women, from high-income countries, examining women's experiences of weight management during pregnancy were included. Meta-ethnography was used to facilitate the meta-synthesis of 17 studies. Results Three themes were identified during the analysis: (1) Awareness and beliefs about weight gain and weight management, which included level of awareness and knowledge about dietary and exercise recommendations, risk perception and decision balance, perceived control over health and weight gain and personal insecurities. (2) Antenatal healthcare, women's experiences of their interactions with healthcare professionals during the antenatal period and the quality of the education received had an effect on women's behaviour. Further, our findings highlight the need for clear and direct information, and improved interactions with healthcare professionals, to better support women's weight management behaviours. (3) Social and environmental influence, the social judgement and stigmatization associated with overweight and obesity also acted as a negative influence in womens' engagement in weight management behaviours. Conclusion Interventions developed to promote and maintain weight management behaviours during pregnancy should consider all levels of influence over women's behaviours, including women's level of awareness and beliefs, experiences in antenatal care, education provision and social influence.